PREDICTIVE DISTINCTIVES TOWARDS ENGAGEMENT IN INCLUSIVE EDUCATION - anine Joy L. Tenerife (Proceedings of International Conference on Special Education, 2021)
Inclusion provides that equal access to quality education is a fundamental right granted to everyone, regardless of the differences, features, and characteristics. Undoubtedly, teachers play an indispensable role in the success of such educational mantra. This research assessed the competency of the regular public elementary school teachers handling inclusive classes; and the benefits of inclusive education during school year 2019 to 2020 in Cebu City to propose an appropriate and relevant development plan. There were 63 respondents who were identified using cluster sampling and were asked to answer the adapted survey questionnaire. The data gathered were organized and treated statistically using frequency count, percentage, weighted mean, Pearson r and multiple regressions. Findings showed that most of the respondents were females whose field of specialization were not aligned with special education and were not exposed to relevant trainings in inclusion. Moreover, the respondents perceived themselves to be highly competent in handling inclusive classes; and viewed inclusive education to be highly beneficial for the learners with and without special needs. There was a significant relationship between the teachers’ competence in handling inclusive classrooms and the benefits of education. Lastly, there was no significant relationship between the respondents’ profile and their perceived competence. Thus, it is highly recommended that the proposed teachers’ development plan of this study be adopted, implemented, and monitored to continuously enhance the teachers’ competence in implementing inclusion for the benefits of the students with or without special needs.